The Use of an Educational Game to Improve Students’ Understanding of Future Perfect and Future Perfect Continuous Tenses - Nanda Ramadani; Aprilia Hutabarat; Jopani Ramadhani; Yulia Armaini; Sevvi Khadijah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
Mastering advanced English grammar can be particularly challenging for young learners, especially when it comes to complex tenses. These difficulties often lead to low engagement and limited retention when taught using traditional methods. This study aims to improve the understanding of the Future Perfect Tense and Future Perfect Continuous Tense among elementary school students through the use of an educational game titled “Future Time Travelers.” The research was conducted at SD Negeri 064037, Medan Tembung. Given the abstract and complex nature of these grammatical structures, young learners often struggle to grasp them through conventional teaching methods. Therefore, this study introduced an interactive, game-based learning approach that integrates storytelling, time-travel missions, and visual aids to contextualize the use of these tenses in a fun and engaging way. Using a classroom action research method, data were gathered through pretests, posttests, teacher observations, and student reflections. The results showed a significant improvement in students’ comprehension and ability to apply both tenses correctly in sentence construction. The educational game not only enhanced their grammatical skills but also increased their motivation and participation during English lessons. This research highlights the effectiveness of game-based learning in making advanced grammar more accessible and enjoyable for young learners.